Evaluation of Antioxidant Activities of Various Solvent Extracts of Fruits and Leaves of Ehretia serrata - Zara, Saman; Ahmed, Dildar; Baig, Hira; Ikram, Muhammad (Asian Journal of Chemistry, 2012)
Ehretia serrata belongs to the genus Ehretia which is well known for its many important biological properties. Different species of Ehretia are used by traditional practitioners for curing several diseases. The present study was aimed to evaluate the antioxidant properties and reducing power of various solvent fractions of fruits and leaves of Ehretia serrata. Ethyl acetate fraction of leaves contain the highest flavonoid (752.753 ± 1.5 μg/mL of rutin equivalent) as well as phenolic content (942.33 ± 2.3 μg/mL of gallic acid equivalent). It is also found to be most active against free radicals and reducing agents when investigated by various assays, i.e., ABTS (TEAC 1.76 ± 0.004 μmol), DPPH (EC50 120.499 μg/mL), FRAP (270.44 ± 1.00 μmol of ascorbic acid equivalent, AAE), Phosphomolybdate (156.92 ± 4.63 μg/mL of AAE) and reducing power assays. However, the ethyl acetate fraction of fruits showed the highest lipid peroxidation value followed by the leaves fraction. The 1-butanolic and chloroform fractions of leaves and ethyl acetate fraction of fruits showed appreciable results in all the assays. The non-polar hexane fractions were less effective against free radicals. The significant correlation coefficient calculated for TEAC, 1/EC50, FRAP and total phenolic content assay indicates the presence of highly active phenolic compounds. An insignificant correlation was found between the total flavonoid and phenolic content. Thus, the findings of this research indicate ethyl acetate fractions of fruits and leaves, to be a possible lead in the discovery of natural antioxidants.